Utilization of Podcasts as an Innovative Media for Indonesian Language Learning (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This article aims to discuss the use of podcasts as one of the innovative media in learning Indonesian. Along with the development of digital technology, the use of audio media such as podcasts is increasingly in demand because of its flexible nature, easy access, and ability to reach various groups of students. This study was conducted to determine how podcasts can be integrated into the Indonesian language learning process, what are their advantages and disadvantages, and how to implement them in the context of actual learning. The main objective of this study is to identify the potential of podcasts as a learning medium, and to analyze the forms of their effective use in improving students' language competence, especially in listening and speaking skills. The method used in this study is a descriptive qualitative method with a literature study and observation approach. Data were obtained through analysis of various relevant literature on the use of podcasts in education, as well as through observation of Indonesian language learning practices involving podcast media. In addition, limited interviews were conducted with teachers and students at the high school level to obtain an initial picture of the acceptance and perception of this media. Data analysis was carried out thematically to identify patterns of use and supporting or inhibiting factors in its implementation. The results of this study are expected to contribute to the development of more innovative learning media, as well as being a reference for educators in integrating audio technology in the Indonesian language learning process.